Financial Development and Economic Growth in Uganda - Kilimani, Nicholas (The IUP Journal of Financial Economics, 2007)
This study provides the empirical findings on the relationship between financial development and economic growth in Uganda from 1970 to 2002. The results support the McKinnon-Shaw hypothesis, which suggests that removal of distortions in the financial sector stimulates economic growth. In Uganda, there have been financial sector reforms since 1992. These factors help to explain the positive relationship between financial development and economic growth in the country. The study uses a dummy variable to examine the effect of financial sector reforms. The coefficient of the dummy variable is positive and significant, implying that the changes induced by the liberalization of the economy had a positive impact on real economic growth in Uganda
Keywords: Financial Development; Economic Growth